The Effectiveness Of The Flipped Classroom Learning Method In Improving Students’ Learning Outcomes In Arabic Language Subjects - Shofiatun Athriani; Asriandi asriandi; Idiatussaufiah (The Center for Language Development, Mataram State Islamic University., 2025)
This study aims to determine the effectiveness of applying the Mastery Flipped Classroom learning method on students’ Arabic learning outcomes in the eleventh grade at MAS Mu’allimin NW Pancor. The Mastery Flipped Classroom method reverses the traditional learning pattern by providing materials through videos or learning resources before face-to-face sessions, allowing students to learn at their own pace and level of understanding (self-paced learning). During classroom sessions, the teacher acts as a facilitator who guides students through comprehension and enrichment activities until they reach a certain level of mastery.This research employed a quantitative approach with a True Experimental design. The research design was used a control group design involving two groups: the experimental class and the control class. Data were collected through learning achievement tests and interviews. Data analysis included normality tests, linearity tests, and t-tests using SPSS Statistics version 25. Based on the results of data analysis, the experimental class obtained an average pre-test score of 69.03 and an average post-test score of 78.2, while the control class obtained an average pre-test score of 72.5 and an average post-test score of 77.6. Furthermore, the hypothesis test showed that tcount < ttable (0.229 < 2.009), indicating that H₀ was accepted and Ha was rejected. Therefore, it can be concluded that there is no significant effect of the Mastery Flipped Classroom method on students’ Arabic learning outcomes. The results showed an increase in the average score in the experimental class after applying the flipped classroom method; however, the improvement was not statistically significant. Thus, this method has not been proven to be more effective than conventional learning. Factors that may have influenced these results include the limited sample size, differences in students’ initial abilities, and the short duration of implementation. Moreover, some students did not fully engage in independent learning activities before class, reducing the effectiveness of the method. Nevertheless, the flipped classroom approach still had a positive impact on students’ understanding of the learning material.